1967
DOI: 10.1143/ptp.38.1326
|View full text |Cite
|
Sign up to set email alerts
|

Partial Wave Amplitudes of the Reaction π-+p→ η +n

Abstract: Energy dependent partial wave anlyses for the reaction rc-+p ':"'J+n are carried out with respect to S, P, D and F waves in the energy range 561-1300 MeV. Two different types of the solutions are obtained. In the first solution, the "'J-production peak is dominated by the S 11 resonance with mass M = 1570 MeV, total width TT = 140 MeV, branching ratios (S 11 res. --->rcN) I (S 11 res.->all) =40% and (S 11 res.-----'7"1JN)/(S 11 res.--'lall) =50%. In the second solution, it is dominated by the P 11 resonance wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

1969
1969
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 4 publications
1
17
0
Order By: Relevance
“…One of the present authors (N. S.) improved and tuned the parameters of URASiMA so as to realize an equilibrium state of hadrons for temperatures in the rande 100 -180 MeV for nuclear densities near twice the normal nuclear density. 7) In Ref. 7), equilibration of the system is discussed in detail and thermodynamical quantities are analyzed.…”
Section: §1 Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the present authors (N. S.) improved and tuned the parameters of URASiMA so as to realize an equilibrium state of hadrons for temperatures in the rande 100 -180 MeV for nuclear densities near twice the normal nuclear density. 7) In Ref. 7), equilibration of the system is discussed in detail and thermodynamical quantities are analyzed.…”
Section: §1 Introductionmentioning
confidence: 99%
“…7). Figure 1 displays the obtained equation of state (the pressure P as a function of the energy density ε).…”
Section: §1 Introductionmentioning
confidence: 99%
“…Generalization of the model is an interesting issue. Furthermore, stability of the solutions should be clarified from various points of view [20][21][22][23][24].…”
Section: Summary and Discussionmentioning
confidence: 99%
“…By comparison of the energies, it was shown that if the charge of the matter field is greater than a critical value, a Q-ball is stable against dispersion into free particles and against decay into two smaller Q-balls. In addition to the analysis in this paper, it is important to investigate the stability in various view points [22][23][24][25][26][27].…”
Section: Summary and Discussionmentioning
confidence: 99%